The rationale of using mesenchymal stem cells in patients with COVID-19-related acute respiratory distress syndrome: What to expect. (21st July 2020) - Can, Alp; Coskun, Hakan
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-caused coronavirus disease 2019 (COVID-19) pandemic has become a global health crisis with an extremely rapid progress resulting in thousands of patients who may develop acute respiratory distress syndrome (ARDS) requiring intensive care unit (ICU) treatment. So far, no specific antiviral therapeutic agent has been demonstrated to be effective for COVID-19; therefore, the clinical management is largely supportive and depends on the patients' immune response leading to a cytokine storm followed by lung edema, dysfunction of air exchange, and ARDS, which could lead to multiorgan failure and death. Given that human mesenchymal stem cells (MSCs) from various tissue sources have revealed successful clinical outcomes in many immunocompromised disorders by inhibiting the overactivation of the immune system and promoting endogenous repair by improving the microenvironment, there is a growing demand for MSC infusions in patients with COVID-19-related ARDS in the ICU. In this review, we have documented the rationale and possible outcomes of compassionate use of MSCs, particularly in patients with SARS-CoV-2 infections, toward proving or disproving the efficacy of this approach in the near future. Many centers have registered and approved, and some already started, single-case or phase I/II trials primarily aiming to rescue their critical patients when no other therapeutic approach responds. On the other hand, it is also very important to mention that there is a good deal of concern about clinics offering unproven stem cell treatments for COVID-19. The reviewers and oversight bodies will be looking for a balanced but critical appraisal of current trials. : Abstract : The therapeutic potential of mesenchymal stem cells in acute respiratory distress syndrome-developed COVID-19 cases was tested in recently approved clinical trials. They possess several features facilitating the resorption of the alveolar exudate by type I and type II alveolar cells and improving the pulmonary microenvironment, thus recovering the lung functions in COVID-19 patients.